Suitability Study in UAV Application for UTHM Golf Driving Range - Zulkafeli, Zulhaizat; Mohd Salleh, Anuar (Recent Trends in Civil Engineering and Built Environment, 2022)
The course of photogrammetry also plays an important role in the field measurement and map production. This field is parallel with the development of hardware and software technologies. Recently the technology of Unmanned Aerial Vehicle (UAV) system has developed rapidly. Indirectly, it has increased the application of UAV for various application especially in the course of close range topography and mapping application. This method can be used as an alternative to mapping application because it has advantages in term of time, cost and weather constraint. However, the suitability of golf golf using the UAV system is questionable due to it less ventured. Therefore the aim of this study is to generate a profile for golf UTHM field and to determine the suitability of the area profile as a golf field. In this study, the aerial photographs are acquired using digital camera located on a UAV and controls altitude 50.0 metre to 100.0 metre from the surface ground. The UAV is very suitable for small study area with the limited time and budget project. The acquired aerial photographs were processing using Agisoft PhotoScan Proffesional software to generate profile and topography. Based on this profile and topography data, the analysis will be performed to determine whether the golf UTHM field is suitable for continued functioning as a golf field. UTHM golf target area is 300 x 90 meters. The proposal of this study should focus on the development of a database for sports and recreation areas, especially in the structural plan to enable the analysis to be carried out more effectively. According to more specific criteria with a small area, the contractor needs to add nets around the UTHM golf range so that the golf ball does not exceed the area.